ANALISIS DAN EVALUASI FAKTOR AMPLIFIKASI PERCEPATAN PUNCAK GEMPA DI PERMUKAAN TANAH - Fahmi Aldiamar; M Ridwan; M. Asrurifak; Masyhur Irsyam (Direktorat Bina Teknik Jalan dan Jembatan, 2010)
Earthquake resistant infrastructure planning, generally require the acceleration data at ground level. Currently, the American Society of Civil (ASCE) 07-2010 provides amplification factor for earthquake resistant building design needs so that planners can get the acceleration of the surface by multiplying the value of the accelaration of Infonsesian Earthquake Maps 2010 with the amplification factor. To evaluate the amplification facttor with the seismic hazard analysis using software USGS PSHA-07, evaluation using grid analysis in Sumatra was done using variations of shear wave velocity(VS) which represents the ASCE 07-10 sites classification for very dense soil and soft rock (SC), the soil medium (SD) and soft soil (SE). According to the amplification factor comparison between analysis result and the ASCE 07-2010 at two reviewed period (PGA and 0.2 sec), the SC and SD site result show a close amplification factor to ASCE 07-2010. While large deviation occur between analysis and ASCE 07-2010 at SE site and period T = 1sec with VS30 < 175m/sec. The large deviation probably caused by modeling limitation which only can used specified attenuation function that represent fault zone only. To gain the good quality amplification factor, it is advice to do specific dynamic reponse analysis using local soil condition according to ASCE-07-2010 classification. Keyword : Seismic hazard analysis, amplification factor, peak surface acceleration, surface spectrum response.